Synthesis and antioxidant evaluation of lipophilic oleuropein aglycone derivatives. Issue 12 (21st November 2017) - Nardi, M.; Bonacci, S.; Cariati, L.; Costanzo, P.; Oliverio, M.; Sindona, G.; Procopio, A.
Abstract : A set of oleuropein aglycone derivatives were synthesized by transacetalization under mild and environmental friendly conditions. The antioxidant activities of the obtained compounds exhibited a dependence on their level of lipophilicity thus demonstrating their potential application as a preservative in fatty foods. Abstract : Oleuropein is the most important phenolic compound present in olive cultivars, but it is scarcely present in extra virgin olive oil (EVOO) due to its high hydrophilicity and degradability. Thus, a set of oleuropein aglycone derivatives were synthesized by transacetylation under mild conditions with the aim of circumventing these drawbacks and making the active moiety in oleuropein suitable to be added to food fats. The oleuropein aglycone (closed ring form) is obtained by hydrolyzing oleuropein using Lewis acid catalysis. Then, the permeation profiles as well as the antioxidant capacity of the oleuropein aglycone derivatives were evaluated by ORAC, DPPH assays and by ROS formation using the SH-SY5Y cell line. The biological activities of the obtained compounds exhibited a dependence on their level of lipophilicity.